From Idea to Organization: The Women’s Movement in West Kalimantan, 1926-1945 - Prabowo, Mohammad Rikaz (Universitas Tanjungpura, 2026)
The course of the national movement in West Kalimantan was actually filled with various elements of struggle and activism, including by women. Unfortunately, the existing historiography still does not provide a balanced place for the narrative of women's involvement. This study aims to describe the women's movement in West Kalimantan between 1926 and 1945, which began with ideas in newspapers and transformed into organizations. By using a historical method consisting of the following stages: heuristics, criticism, interpretation, and historiography, the following facts were obtained. Approaching 1926, the existing women's movement was still in the form of ideas in local newspapers in West Kalimantan, with the central issue raised being educational opportunities. Women's organizations emerged to enhance the organization of the movement and collectively implement existing ideas. Several women's organizations that emerged include Aisyiyah (1927), PKIIP (1932), PIIP (1938), PERKIS (1939), and PKIM (1941). In general, the women's movement in this period focused on the struggle in the social field, such as the establishment of courses for women, public health, non-formal education, and the collection of zakat and charity funds. The results of this study are expected to contribute to the historiography of the history of the women's movement in general and become a source of inspiration to continue to pay attention to the fulfillment of the rights of their people today.